Prevalence, awareness, treatment and control of hypertension in Malaysia: A national study of 16,440 subjects. - Gyanchand Rampal, Lekhraj Rampal; Md. Zain, Azhar; Rampal, Sanjay; Rahman, Abdul Rashid (WB Saunders, 2008)
Study design: A cross-sectional study was conducted in all states of Malaysia to determine the prevalence, awareness, treatment and control of hypertension. A stratified two-stage cluster sampling design with proportional allocation was used.